Aktualisasi Nilai-Nilai Pendidikan Islam pada Surat Al-Alaq Ayat 1-5 dalam Pembelajaran Agama Islam - M. Afiqul Adib (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2022)
This study aims to examine the surah al-Alaq verses 1-5 about the virtues of reading, writing, investigating, examining, and including all work for the sake of Allah. In addition, this research will also look for the values ​​of Islamic education contained therein and how to actualize them in learning. This type of research is library research with the data analysis technique used is content analysis. The collection of library materials and the object of discussion under study were made coherently and then re-examined with one another with a predetermined framework. In this study, it was found that Surah al-Alaq verses 1-5 contain three values ​​of Islamic education. These values ​​are Aqidah Education to strengthen belief and faith, Shari'a Education as a guide to facilitate carrying out Allah's commands, and Moral Education as the actualization of carrying out His commands. This first revelation can be used as a guide when the learning process is in accordance with the existing stages.